2019
DOI: 10.1177/2333794x19878062
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Children’s Screen Viewing Time and Parental Role in Household Context

Abstract: Limited screen time has been recommended by the American Academy of Pediatrics for all children and no screen time for children under 2 years of age. With the advancement in technology, the prevalence and detrimental effects of excess screen time on children has become a global problem that can lead to health issues such as obesity and other cardiovascular diseases among both adults and children. This article examines the drivers of screen-related sedentary behavior within the home context and reports on paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
2
20
0
2
Order By: Relevance
“…76% of the participants reported that their children were inactive due to excessive screen time in the study by Nwankwo F et al, (2019). 9 In this study 84.3% of the participants felt that reduced physical activity is an adverse effect of excessive screen time and 83.6% believed that excessive screen time can lead to overweight and obesity.…”
Section: Aware Of Guidelinesmentioning
confidence: 60%
See 1 more Smart Citation
“…76% of the participants reported that their children were inactive due to excessive screen time in the study by Nwankwo F et al, (2019). 9 In this study 84.3% of the participants felt that reduced physical activity is an adverse effect of excessive screen time and 83.6% believed that excessive screen time can lead to overweight and obesity.…”
Section: Aware Of Guidelinesmentioning
confidence: 60%
“…This is similar to the study by Nwankwo F et al, (2019) where 84% were concerned that their children are spending a lot of time using screen devices. 9 Hinkley T et al, in their study on parental perception of screen time in children noted that there were mixed perceptions of screen time, with benefits such as learning, education and relaxation, and risks including habit formation, inappropriate content, negative cognitive and social outcome, and detriments to health. 10 In the study by Hamilton K et al, exploring parent's beliefs about young children's screen time behaviors, improved family interactions and improved child behavior were perceived be advantages and mess and noise factor and increase in parental distress were found to be disadvantages of limiting screen time duration in children.…”
Section: Aware Of Guidelinesmentioning
confidence: 99%
“…Although there were weak correlations between weight and other variables for the male students, these were considered insignificant based on the large sample size. Some studies have related adolescent students’ obesity to SD overuse and the subsequent sedentary lifestyle [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interview questions were designed based on a review of the literature on related topics [ 2 , 17 , 18 ]. The interview guide aimed to achieve the objectives of the study ( Textbox 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the extant literature, most studies have used a quantitative approach to investigate parents’ perceptions of mobile technology use and its effects on their preschool children’s patterns of use [ 15 , 16 ], parents’ concerns [ 17 ], and parent-adolescent social relationships [ 2 ]. One previous study used a combined quantitative and qualitative approach to examine children’s routine behaviors regarding screen time from their parents’ perspectives and how the parents intervened to reduce the children’s sedentary lifestyle behavior [ 18 ].…”
Section: Introductionmentioning
confidence: 99%